Juvenile dermatomyositis with rare cutaneous manifestation: generalised hypertrichosis - Kayani, Maham; Khalil, Elma; Sultan, Javeria; Sagheer, Farah (Journal of the Pakistan Medical Association, 2023)
Juvenile dermatomyositis (JDM) is a rare autoimmune disease characterised by inflammation of muscles and skin with extra muscular involvement of joints, heart, intestine, and liver. Pathogenesis of JDM is believed to be due to vasculopathy. Along with classic cutaneous features of JDM, rare findings include hypertrichosis, lipoatrophy, photosensitivity, bullous lesions, and hyperhidrosis. We present, here, a case of JDM with hypertrichosis as very few cases have been reported previously. Keywords: Juvenile dermatomyositis, Hypertrichosis, Autoimmune disease.